Potential-resolved wavelength tunable electrochemiluminescence from graphitic carbon nitride heterostructure. (10th July 2022) - Chen, Lichan; Wei, Jingjing; Zhao, Panpan; Tian, Libing; Zhou, Shu-Feng
Abstract: Biocompatible and water-dispersible electrochemiluminescence (ECL) phosphors with potential/spectrum-resolved ECL emission are highly desired to underpin ECL-based multiplex detection in a spot-free format. In this work, we develop a band structure engineered graphitic carbon nitride, CN425 -PDI0.5, to achieve potential-resolved wavelength tunable ECL emission. The covalent incorporation of pyromellitic diimide (PDI) with high electron affinity and mobility endows CN425 -PDI0.5 with the coexistence of polymeric melem motifs and melem-PDI motifs. The melem-PDI motifs show lower lowest unoccupied molecular orbital energy level and narrower bandgap, as compared to polymeric melem motifs. By pulsing the CN425 -PDI0.5 nanosheets modified glassy carbon electrode at the increasing reduction potential in phosphate buffer solution containing S2 O8 2‒ as coreactant, the cathode ECL gradually tunes the maximum emission wavelength from 540 nm to 440 nm. The CN425 -PDI0.5 nanosheets with potential-resolved wavelength tunable ECL emission may provide a promising prospect for promoting solid-state ECL-based multiple detection and extending CN application in the sensing fields.